Crescent Dawn: Dirk Pitt # 21 - Cussler, Clive; Cussler, Dirk; Brick, Scott (New York : Penguin Audio, 2010)
NUMA director Dirk Pitt searches for the connections among newly discovered Roman artifacts, the rise of a fundamentalist movement, and the existence of a mysterious long-lost "manifest," which, if discovered again, may change the history of the world.
Unabridged.
Compact discs.
Read by Scott Brick.
Keywords: Pitt, Dirk (Fictitious character) -- Fiction; Marine biologists -- Fiction; Marine engineers -- Fiction; Suspense fiction; Audiobooks